Relationship Between Husband Support and the Use of Postpartum Contraceptives: A Literature Review - Nova Anggaraini; Is Susiloningtyas (Universitas Duta Bangsa Surakarta, 2026)
The postpartum period is a critical phase in reproductive health because the risk of closely spaced pregnancy increases when appropriate contraception is not used. The coverage of postpartum contraceptive use remains suboptimal and is influenced by multiple factors, including husband support in the decision-making process. This study aimed to analyze the relationship between husband support and the use of postpartum contraception based on recent empirical evidence. Methods: This study applied a literature review method by analyzing 10 research articles obtained from PubMed, Google Scholar, and ScienceDirect using the keywords